Volatility Clustering, Risk-return Relationship and Leverage Effect in Indian Public Sector Banks' Returns - Dr. Vandana Dangi (Ramanujan International Journal of Business and Research, 2017)
The public sector banks in India play dominant role in deposit mobilisation and loan advancement to masses due to their capital potency, technological advancement and financial inclusion ideology. Indian investors consider this sector as a reliable investment alternative. They need to evaluate the sector in terms of risk as well as return.The prediction of impact of news on volatility in banking stocks is also vital for investors to measure the risk exposure in their investment. The present treatise is an attempt to investigate the volatility clustering, risk-return relationship and leverage effect in daily Indian public banking sector indices of Nifty PSU Bank. The indices for the period of January 2004 to October 2016 are taken from the database (online) maintained by the National Stock Exchange Ltd. The data was studied for stationarity and autoregressive conditional heteroscedasticity with the help of Ng-Perron tests, Augmented Dickey- Fuller test, Engle's ARCH test and Breush-Godfrey-Pagan test respectively. The results confirmed that the return series are stationary and ARCH effect is present in return series. GARCH-M was applied to study the risk-return relationship and EGARCH model was employed to study the leverage effect in Nifty PSU Bank return series. The results confirm the presence of highly persistent volatility and asymmetric leverage effect in public banking sector return series. But there is no evidence of risk-return relationship in the series. These findings may help the investors in understanding the risk exposure of their investment in Indian public sector banks and framing their investment strategy to hedge risk in better way.